2023
DOI: 10.1155/2023/6678211
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chest Anteroposterior Radiography with Computed Tomography in Patients with Blunt Chest Trauma

Abstract: Background. In cases of chest trauma, computed tomography (CT) can be used alongside chest anteroposterior (AP) radiography and physical examination during initial evaluation. Performing a CT scan may be difficult if a patient has unstable vital signs. In contrast, radiography may not always reliably diagnose nonmarked pneumothorax or extensive subcutaneous emphysema. Objectives. This study aimed to determine the agreement between chest radiography and CT findings in patients with blunt chest trauma. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…In addition, the delay of medical services after the earthquake and long transfer times to the nearest active hospitals also increase the number of deaths. [4,[7][8][9][10][11] In our study, no mortality rate was observed in thoracic trauma. Except for our mortality rate, the median time to stay under the rubble and the median transfer times were similar to the studies in the literature.…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, the delay of medical services after the earthquake and long transfer times to the nearest active hospitals also increase the number of deaths. [4,[7][8][9][10][11] In our study, no mortality rate was observed in thoracic trauma. Except for our mortality rate, the median time to stay under the rubble and the median transfer times were similar to the studies in the literature.…”
Section: Discussioncontrasting
confidence: 41%